Copper-catalyzed one-pot synthesis of 2-(2, 2, 2-trifluoroethyl)-substituted benzofused heterocycles. Issue 9 (5th March 2021) - Wu, Wei; Luo, Beibei; You, Yi; Weng, Zhiqiang
Abstract : A method for copper-catalyzed synthesis of 2-trifluoroethyl-substituted benzofurans and indoles from the reaction of salicylaldehyde/2-aminobenzaldehyde p -tosylhydrazones with 2-bromo-3, 3, 3-trifluoropropene has been developed. Abstract : A novel synthesis approach for the construction of 2-trifluoroethyl-substituted benzofurans under copper-catalyzed conditions has been developed. The reaction of salicylaldehyde p -tosylhydrazones with 2-bromo-3, 3, 3-trifluoropropene proceeded through a sequential process to afford products in moderate to excellent yields (up to 93%). This method is also applicable to the formation of 2-trifluoroethylated indoles.